Annual Report of the Park Department, Boston Department of Parks 86 (1887) - (:unkn) unknown (My University, 1886)
Park Ordinances, § 3: Prohibited carry of firearms, throwing stones, or other missiles within the parks of the city.
Keywords: SENSITIVE PLACES